Coordinated functions of WSS1, PSY2 and TOF1 in the DNA damage response - O'Neill, Bryan M. (Oxford University Press, 2004)
The stabilization and processing of stalled replication forks is required to maintain genome integrity in all organisms. In an effort to identify novel proteins that might be involved in stabilizing stalled replication forks, Saccharomyces cerevisiae mutant wss1Δ was isolated from a high-throughput screening of ∼5000 deletion strains for genes involved in the response to continuous, low-intensity UV irradiation. Disruption of WSS1 resulted in synergistic increases in UV sensitivity with null mutants of genes involved in recombination (RAD52) and cell cycle control (RAD9 and RAD24). WSS1 was also found to interact genetically with SGS1, TOP3, SRS2 and CTF4, which are involved in recombination, repair of replication forks and the establishment of sister chromatid cohesion. A yeast two-hybrid screen identified a potential physical interaction between Wss1 and both Psy2 and Tof1. Genetic interactions were also detected between PSY2 and TOF1, as well as between each gene and RAD52 and SRS2, and between WSS1 and TOF1. Tof1 is known to be involved in stabilizing stalled replication forks and our data suggest that Wss1 and Psy2 similarly function to stabilize or process stalled or collapsed replication forks.